1995
DOI: 10.1021/j100011a006
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Calculations of Vibrational Frequencies and Infrared Intensities for Global Warming Potential of CFC Substitutes: CF3CH2F (HFC-134a)

Abstract: We have investigated the feasibility of using ab initio molecular orbital methods for predicting the global warming potential of the proposed chlorofluorocarbon (CFC) substitute CF3CH2F, HFC-134a. Various levels of theory and basis sets were used to optimize geometry and calculate harmonic vibrational frequencies and infrared intensities for the molecule using the GAUSSIAN 92 software package. In attempting to assess the quality of the computations, we found it necessary to reconsider the vibrational assignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 4 publications
(6 reference statements)
2
44
0
Order By: Relevance
“…Details of these calculations are provided by Papasavva et al [1995Papasavva et al [ , 1996Papasavva et al [ , 1997 and ?apasavva [1997]. We have investigated a variety of levels of theory and found that the second-order MollerPiesset perturbation theory, using the 6-31G** basis set, MP2/6-31G**, represents a reasonable compromise between the accuracy of method and the limitations of size (of which the total number of electrons is the most useful gauge) of molecular systems that can be computed.…”
Section: Methodsmentioning
confidence: 99%
“…Details of these calculations are provided by Papasavva et al [1995Papasavva et al [ , 1996Papasavva et al [ , 1997 and ?apasavva [1997]. We have investigated a variety of levels of theory and found that the second-order MollerPiesset perturbation theory, using the 6-31G** basis set, MP2/6-31G**, represents a reasonable compromise between the accuracy of method and the limitations of size (of which the total number of electrons is the most useful gauge) of molecular systems that can be computed.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, this parameter was determined from degradation rates and infrared vibrational spectroscopy but recently, theoretical approaches have been used to estimate GWPs. Papassavva et al [76] used ab initio computations of vibrational frequencies and infrared intensities to calculate the GWP of CF 3 CH 2 F. The calculated harmonic frequencies using MP2/6-31G(d,p) method agreed with the experimentally observed frequencies below 800 cm -1 . The calculated absolute intensities were in good agreement (better than 10 %) with the limited experimental measurements previously reported.…”
Section: Global Warming Potentialmentioning
confidence: 75%
“…The computational results have been used to assign the structures observed in the experimental valence photoelectron spectrum of 1,1,1,2-tetrafluoroethane. Previous theoretical studies have included the calculation of the equilibrium geometry [30,31] and have been compared with experimental results, for example, with microwave spectroscopy by Ogata et al [32]. Due to 1,1,1,2-tetrafluoroethane's atmospherical abundancy, studies reported by Papasavva et al [30,31] concentrated on calculating vibrational frequencies and infrared intensities in order to estimate the global-warming potential of the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Previous theoretical studies have included the calculation of the equilibrium geometry [30,31] and have been compared with experimental results, for example, with microwave spectroscopy by Ogata et al [32]. Due to 1,1,1,2-tetrafluoroethane's atmospherical abundancy, studies reported by Papasavva et al [30,31] concentrated on calculating vibrational frequencies and infrared intensities in order to estimate the global-warming potential of the molecule. The calculated results presented by Zhou et al [28] included also the minimum-energy geometry of both the neutral and cationic ground state of 1,1,1,2-tetrafluoroethane, as well as enthalpies of formation of the molecule and its fragments.…”
Section: Introductionmentioning
confidence: 99%